Pola Pewarisan Nilai yang Berimplikasi Bimbingan pada Pancakaki Bani Nuryayi - Hidayat, Ade (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2017)
One of family functions is to maintain relationship among generations, where the prior generation leaves the influence to the next generation. The family system built then become widespread, not only has two generations but unfold to many generation in building kinship system. The kinship system in Sundanese culture is known as Pancakaki. The individual and social function of pancakaki varies in each period, so that in historical period, society of Sundanese are able to keep values of Sundanese established by their own social system. Pancakaki not only strengthens cultural identity of ancestor heritage, but also as a means for preparing, maintaining and developing a collaboration relation among members based on their values. As an example of the implementation of the pancakaki, Bani Nuryayi kept strongly maintains tradition that was taught by Kyai Nuryayi. This inheritance is sustainable by using patron-client approach. Therefore, pancakaki becomes an effective education pattern for inheritance of cultural values and tradition to the next generation. The implication on Guidance and Counseling that Pancakaki system as an exclusive means of family as coordinate institution for school in order to support optimalitation of personality development and integrity of student identity.